What Determine Customer Loyalty at Tokopedia Website? - Steven Sanjayai , Louis; Sulistiowati,; Bintoro Bagus Purmono,; Helma Malini,; Erna Listiana, (International Journal of Scientific Research and Management (IJSRM), 2023)
With the advent of online shopping in Indonesia, e-commerce has emerged as a transaction platform for purchasing goods and services for the community. The development of e-commerce trends has led to intense business competition in cyberspace. Website quality is one of the factors that can determine trust and generate online shop customer loyalty. In an increasingly competitive environment, e-retailers are required to build quality that affects customer trust. Customer loyalty presents a paradox. This study uses a causal design approach to examine the relationship between the independent variables and the dependent variable using Structural Equation Modeling (SEM) with the AMOS 24 application.